Asuhan Kebidanan Continuity of Care pada Ny. T G2P1A0 Umur 30 Tahun di Wilayah Kerja Puskesmas Bergas - Andini Putri; Luvi Dian Afriyani (Universitas Ngudi Waluyo, 2025)
Continuity of care is the provision of midwifery care from pregnancy, childbirth, postpartum, neonate until deciding to use family planning. This aims to help monitor and detect the possibility of complications that accompany the mother and baby from pregnancy until the mother uses family planning. Midwifery care methods in the Bergas Health Center Working Area. and through home visits by providing counseling according to the mother's needs. Midwifery care provided to Mrs.